3D Multi-Material Laser Powder Bed Fusion of 420 stainless steel-Cu parts for Plastic Injection Mold Inserts - Cunha, Ângela Sofia Varela (2023)
Plastic injection molding is one of the fastest-growing industries in the world. However, although it presents numerous advantages, the costs associated with the mold and machine are high and, therefore, this process is only profitable for mass production. Moreover, the reduction in the cycle time, more specifically the cooling time, has been a never-ending challenge since it has a direct influence on production costs. This study is focused on the production of 420 stainless steel-copper solutions by 3D multi-material laser powder bed fusion. This novel material’s design concept allows combining the high mechanical resistance of the steel alloy and the high thermal conductivity of the copper. The processing parameters and strategies as well as the transition zone between these materials are of the most challenging and important aspects both from a mechanical and metallurgical point of view. The obtained results show that this approach is effective to produce inserts of copper in a 420 stainless steel capable of improving the in-service conditions of a plastic injection mold, enhancing its performance and life.